Moses Mendelssohn's metaphysics and aesthetics - Munk, Reinier (Studies in German idealism, 2011)
This book presents an extended dialogue in essay form between specialists in the work of Moses Mendelssohn, and experts in important trends in related late-seventeenth and eighteenth century thought. The first group of contributors explores themes in Mendelssohn's metaphysics and aesthetics, presenting both their internal argumentative coherence and their historical context. The second outlines the context of Mendelssohn's views on specific topics, and describes his contribution to the discussion of them. The essays are organized in four sections. The first pairs two essays on Mendelssohn's theory of language and writing. The second section offers three essays addressing a number of topics in Mathematics and philosophy in Mendelssohn. A group of eight essays follows, dealing with Metaphysics in a historical context. The fourth section presents five essays discussing Mendelssohn's Aesthetics in a historical context. Moses Mendelssohn's Metaphysics and Aesthetics arises from a conference held in Amsterdam in 2009, which gathered numerous authorities to address the central theme. Taken together, these eighteen essays present a sophisticated portrait of Mendelssohn, packed with detail and rich in complexity. - publisher's description.